Association between Sleep Disturbance with Weight-for-Height and Body Mass Index in Preschoolers - Laili Nur Rosyidah; Ahmad Suryawan; Irfiansyah Irwadi (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Hormonal changes affecting a child's growth occur in deep sleep phase of preschoolers. Nowadays, obesity is still a world health problem. In 2014, Indonesia had three growth problems, one of them was overweight in preschoolers. This study aimed to analyze the association between sleep disturbance with weight-for-height and body mass index (BMI) in preschoolers. Methods: This was a cross-sectional study by analyzing the tendency with boxplot charts and the association was measured by Mann-Whitney test and independent t-test. Data of 86 preschoolers aged 3-5 years old were obtained from three kindergartens in Kalijudan, Surabaya from March to September 2018. Z-score values and the categories of weight-for-height Z-score (WHZ) and BMI-for-age Z-score (BAZ) refer to WHO Standards 2006 and sleep disturbances were measured by sleep disturbance scale for children (SDSC) questionnaire. Results: 65.12% of preschoolers had sleep disturbance and 66.28% of them had normal WHZ and BAZ. The average WHZ and BAZ value in preschoolers who had sleep disturbance (M = -0.2730; -0.2207) were higher than preschoolers who had no sleep disturbance (M = -0.6083; -0, 5920). Results from Mann-Whitney test showed the same significance value between WHZ and BAZ, p = 0.226. Independent t-test showed a significance value of p = 0.524 and p = 0.490, meaning that there was no statistically significant association. Conclusion: There was no statistically significant association between sleep disturbance with WHZ and BAZ in preschoolers aged 3-5 years old, however descriptively, the values of WHZ and BAZ in the group of preschoolers who had sleep disturbance tended to be higher.